RYE (SECALE CEREALE L.) PHENOLIC COMPOUNDS AS HEALTH-RELATED FACTORS - Dynkowska, Wioletta M. (Plant Breeding and Seed Science, 2019)
The diversity of phenolic compounds found in rye grain makes this cereal the valuable source of these substances in everyday food. Simple phenolic compounds, as well as their metabolites, show a pro-health effect. Phenolic acids and ferulic acid dehydrodimers are included in the group of cereal antioxidants. The antioxidant activity of phenolic compounds is an essential factor in the prevention of cancer and cardiovascular diseases.